K+ATP channels-independent analgesic action of Crotalus durissus cumanensis venom - Pereira, Ticiana Praciano; Campos, Adriana Rolim; Leal, Luzia Kalyne A. M.; Pierdoná, Taiana Magalhães; Toyama, Marcos H. [UNESP]; Monteiro, Helena Serra Azul; Martins, Alice Maria Costa (SAGE Publications, 2010)
The effect was investigated of the K+ channel blocker, glibenclamide, on the ability of Crotalus durissus cumanensis venom (CDCM) to promote peripheral antinociception. This was measured by formalin-induced nociception in male Swiss mice. CDCM (200 and 300 μg/kg) produced an antinociceptive effect during phase 2 in the formalin test. The effect of CDCM (200 μg/kg) was unaffected by the ATP-sensitive K+ channel blocker glibenclamide (2 mg/kg). These results suggest that CDCM is effective against acute pain. However, the ATP-sensitive K+ channels pathway is not contributable to the antinociceptive mechanism of CDCM.
Keywords: Crotalus durissus cumanensis venom; Glibenclamide; Nociception